Spectrum of the Gallbladder Diseases in a Teaching Hospital of Lahore, Pakistan – 20 Years Experience (Medical Forum Monthly, 2020)
Objective: To document the prevalence and the histologic pattern of gallbladder diseases in our setup.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Histopathology, Gulab Devi Hospital, Lahore from January 1996 to December 2015.Materials and Methods: Our study consisted of 1083 consecutive cholecystectomy specimens, received in 20 years (1996 to 2015) by the Department of Histopathology, Gulab Devi Hospital, Lahore, Pakistan. Cholecystectomy accounted for 9% of the total operations during the study period. The patients’ medical and histopathology records were entered in Proforma. Their age, sex, clinical complaints, history of gall stones and histological diagnosis was entered accordingly.Results: There were 921(85.04%) females and 162(14.96%) males. The male to female ratio was 1:5.7. The pathologies were divided mainly in two groups: Non-malignant lesions numbered 1027 (94.8%) while the malignant lesions were 56 (5.17%). The main underlying complaints were pain in right hypochondrium 1018 (94%), nausea/vomiting 353 (33%) and jaundice 21 (2%) cases. The ages ranged from 7 to 93 years.Conclusion: Gallbladder pathologies are very common in Central part of the Pakistan. We found that rate of malignancies in this study is much higher than those in the northern areas of the country.